Agricultural Development and Tenancy Disputes in Japan, 1870-1940 - RICHARD J. SMETHURST (Princeton University Press, 2014)
LIKE most of us who first studied Japanese history in the 1950s and 1960s, I learned that the peasantry paid a heavy price as Japan modernized. We were taught that the Meiji government in the nineteenth century financed the creation of its military and industrial machine by the only means possible, an exploitative land tax, and that in the process Japanese peasants fell more and more deeply into debt even as the nation grew in wealth and power. By the 1920s and 1930s when Japan moved toward a vicious and ultimately disastrous war, the peasantry had fallen so deeply into tenancy, debt, and poverty that they rose up against their oppressors, the landlords. When poor farmers failed in this effort, they, simple, benighted men, fell prey to the nostrums of young army officers and the radical right, and thus played a role, albeit a passive one, in the road to World War II. Even as I wrote my doctoral dissertation and then revised it for publication as A Social Basis for Prewar Japanese Militarism, I began to have doubts about this interpretation of the countryside. If rural people were suffering to the extent that we learned they were, why did more farm than city boys pass the army's conscription physical examination? How could one explain that a higher percentage of 20-year-olds in rural Iwate, one of Japan's poorest prefectures, passed their physicals in 1934-1935, years of "famine" in its region, than in Tokyo or the nation as a whole? But it was my experiences in the spring of 1969 that finally led me to attempt a reinterpretation of Japan's modern agricultural experience.